Inflammatory factor expression in HaCaT cells and melanin synthesis in melanocytes: Effects of Ganoderma lucidum fermentation broth containing Chinese medicine. Issue 1 (31st December 2022) - Meng, Xianyao; Yang, Yunli; Wu, Yuehang; Zhang, Ying; Zhang, Hongyan; Zhou, Weiqiang; Guo, Miaomiao; Li, Li
ABSTRACT: Ganoderma lucidum possesses anti-inflammatory, antioxidant, and immunomodulatory properties. We evaluated the anti-inflammatory and anti-melanogenesis effects of G. lucidum alone (S1), G. lucidum and Polygonatum odoratum (S2), and G. lucidum and P. ginseng (S3) using an ultraviolet B-irradiated HaCaT cell model and a prostaglandin 2 (PGE2)-treated B16-F10 melanocyte model. S3 inhibited PGE-2 and LL-37 secretion in HaCaT cells and melanin and tyrosinase expression in B16-F10 cells. Furthermore, LC/MS/MS results revealed that the levels of 70 components were higher in S3 than in S1 and S2. These results demonstrate that G. lucidum and P. ginseng co-culture fermentation broth possess in vitro anti-inflammatory and anti-melanogenesis effects; it can be used in the skin care industry.